Filsafat Kelepasan dalam Yoga Sutra Patanjali - Ni Wayan Sumertini (Sanjiwani: Jurnal Filsafat, 2021)
There are many methods for attaining liberation. One of the most famous is the systematized technique by Maharsi Patanjali. This technique can guide every sadhaka from various levels of consciousness. His system of astanga yoga was designed very rigidly from the lowest to the highest human consciousness. This work will critically describe how the stages of Astanga Yoga can be used as a tool to increase everyone's awareness from the lowest to the highest stage. The technique presented is mental technique, which is a technique whose workings are fully in the human mind. The Patanjali Yoga technique works entirely in the realm of psychology. The yama and niyama that were stated earlier were intended to build a basic awareness of the importance of ethical values. The asana techniques in it are only as a support for the mind in order to be able to manage the mind more deeply. While breathing techniques are given in order to train more subtle body systems so that energy is managed within. Furthermore, the given technique has led to a deeper self-awareness so that one is finally able to find one's true self.